An improved economic dispatch procedure for electric power systems - Santos, Rizalino G. (1982)
An improved procedure for solving the economic dispatch problem in electric power systems is presented. The proposed method solves the coordination equations using penalty factors derived from a fast-decoupled loadflow routine. It takes into account constraints on system variables which are beyond the scope of traditional loss-formula procedures. With this procedure, the system model can be readily modified for changes in network configuration and loading. The method is tested using standard five-bus and eleven-bus systems. The results are compared with those obtained using other accepted methods.